PENGEMBANGAN MEDIA MONITU (MONOPOLI WAKTU) UNTUK MENINGKATKAN PEMAHAMAN KONSEP OPERASI HITUNG WAKTU DI KELAS II SD - Endang Sulastri; Abdul Mujib (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to Develop monitu (Monopoly Waktu) learning media that can improve the understanding of the concept of time operations for second-grade elementary school student. This study uses the Research and Development(R&D) met met with the ADDIE model consisten of five stages: analysis,Disign, Development, Implementation and Evaluation. The research subjects were second-grade student of SDN 060796 Medan area Selatan and involved material experts, media experts, and teachers. The reseaech instrument included validation sheets, teacher and student response questionnaires, and a concept understanding test. The results showed that monitu media has a very good level of validity, is effective in improving concept understanding, and is practical for use in mathematics learning. This media Makes learning more fun, interactive, and contextual so that it can increase learning motivation.